Non-tuberculous Mycobacterial Infection of the Musculoskeletal System Detected at Two Tertiary Medical Centres in Henan, China, 2016–2020 - Ma, Qiong; Chen, Rende; Yang, Enhui; Yuan, Youhua; Tian, Yongfu; Han, Yongguang; Wang, Shanmei; Wang, Baoya; Yan, Wenjuan; Zhang, Qi; Jing, Nan; Ma, Bing; et al. (Frontiers in Microbiology, 2021)
Non-tuberculous mycobacterial (NTM) infection of the musculoskeletal system is rare but poses a grave threat to public health. These infections yield non-specific symptoms that remain undetected until the development of the later stages of the disease. In this study, we performed a retrospective review of 25 cases of musculoskeletal NTM infection at two tertiary medical centres over a 5-year period to determine the clinical features to improve the current clinical diagnosis and treatment. The most common mycobacterial species detected were Mycobacterium fortuitum in eleven patients, M. abscessus in eight patients, M. houstonense in three patients, M. avium in two patients, and M. smegmatis in one patient. The sites of infection included the limbs and joints, most commonly the knee (ten patients) and foot (six patients). The median duration from the onset of symptoms to diagnosis was 2.5 months (0.8–13.5 months). Deep sinus tracts extending to the surgical site were observed in 60% of the patients (15/25), and granulomatous inflammation and granulomatous inflammation with necrosis occurred in 60% of the patients (15/25). All patients underwent surgical treatment for infection control, and all patients, except one, received antimycobacterial therapy based on drug sensitivity assays. The median duration of the antimicrobial chemotherapy was 5 months (range: 3–20 months). At the final follow-up, 24 patients presented with absence of recurrence and one patient succumbed owing to heart failure after debridement. Our findings highlight the importance of vigilance and improvements in the diagnostic methods for musculoskeletal NTM infection. Aggressive surgical treatment and antimycobacterial drug treatment can help achieve satisfactory results.